Two new species of Apistogramma Regan (Teleostei: Cichlidae) from the rio Trombetas, Pará State, Brazil - Kullander,Sven O (2005)
Apistogramma angayuara is described from the rio Trombetas close to the cachoeira Vira Mundo where it is found in association with rapids. It is assigned to the A. pertensis species group, distinguished by the following characters in combination: three prominent stripes composed of dark spots along the sides of the abdomen, 2 vs. 3 postlachrymal infraorbital pores, 5 vs. 4 dentary pores, low dorsal fin in adult males, and presence of a caudal spot. It is the smallest species of Apistogramma reported so far, with the largest male 24.7 mm SL and the largest female 22.7 mm SL, and the first cichlid species found with a significant proportion of rhizopods in the stomach content. Apistogramma salpinction is described from lentic habitats at the margin of road BR-163, circa 70 km from Cachoeira Porteira village, in a swamp most probably connected to the igarapé Caxipacoré. It is compared to members of the Apistogramma cacatuoides group with which it shares prolonged anterior dorsal fin lappets and marginal caudal fin streamers in adult males. It is distinguished from all other species of Apistogramma by the color pattern which includes a lateral band and abdominal stripes that become darker and have much lighter interspaces on the caudal peduncle, and a caudal spot that is divided into elongated blotches continuing the lateral band and upper two abdominal stripes, respectively.